Characterization of Sodium Dodecyl Sulphate–degrading Enterobacter cloacae sp. STRAIN AaMa (Journal of Environmental Microbiology and Toxicology, 2023)
Surfactants are substances that can reduce its surface tension during dissolved in water or liquid and produce foam or solid. Bacterial-degrading SDS can be used for the bioremediation of this toxic substance in aquatic bodies or in soil. In this study, the isolation, identification and  characterization of a local SDS-degrading bacterium is reported. Samples were isolated from a local location that had a history in surfactant contamination. Screening results shows that the best SDS-degrader was identified as Enterobacter cloacae sp. strain AaMa. The optimum conditions for the Enterobacter cloacae sp. strain AaMa to degrade the SDS were at pH 7.5, temperature 30 °C and the best nitrogen source to degrade the SDS was sodium nitrate. The Km (app) and Vmax (app) of SDS-degrading enzyme were 0.1035 mM and 0.4851 µmol SDS per minute per mg protein, respectively.
Keywords: Sodium Dodecyl Sulfate; Biodegradation; SDS-degrading bacterium; Enterobacter cloacae; Alkylsulfatase